M HIDUP DAN PERJUANGAN SYEKH YUSUF: HIDUP DAN PERJUANGAN SYEKH YUSUF - rahmatullah, muhammad asep (ISLAMIKA, 2021)
Abstrak In the historical record of Islam in the archipelago, that ulama, sultans, sheikhs and walisongo have a big role and contribution in the struggle for the spread of Islamic teachings. Since the entry of Islam into the archipelago, Islam has been easily accepted by the indigenous population, so that until now its teachings, culture, history and civilization are deeply rooted for all Indonesian Muslims. That all Islamic religion can be perfectly and fully established cannot be separated from the role of the sultans, scholars, sheikhs, walisongo and Indonesian Muslims.One of them is the role of a great scholar who has knowledge, and is highly charismatic, namely Sheikh Yusuf Al-Makasari, whose life and struggle is dedicated to the struggle for da'wah and jihad fi sabillilah to spread Islam. Apart from being a fighter for Islam, Sheikh Yusuf is also a scholar who is active and productive in his worrk. Sheikh Yusuf left his Arabic and Lontar treatises of Sufism writings. Namely Zubdat Al-Asror, Revealing the Essence of All Secrets of Sheikh Yusuf Al-Makassari 1626-1699. Then, Kaifiyat Sufism, namely Al-Barakat Al-Sailaniyyah, Al-Fawa'il Al-Yusufiyyah Fi Bayyan Tahqiq Al-Suffiyah, Hashiyyah, Kifiyat Al-Munghghi Wa Al Ithbat bi Al-Hadith Al-Qudsi which was written in Sri Lanka. Mathalib Al-Salikin.Hopefully Indonesian Muslims can learn from the life history and struggle of Sheikh Yusuf to spread Islamic da'wah for the revival and progress of Indonesian Islam. Keyword : Life, Struggle, Sheikh Yusuf